Graphite reinforced silane crosslinked high density polyethylene: The effect of filler loading on the thermal and mechanical properties. Issue 3 (4th December 2020) - Kourtidou, Dimitra; Symeou, Elli; Terzopoulou, Zoi; Vasileiadis, Isaak; Kehagias, Thomas; Pavlidou, Eleni; Kyratsi, Theodora; Bikiaris, Dimitrios N.; Chrissafis, Konstantinos
Abstract: Crosslinked polyethylene is a promising polymer regarding its mechanical properties and wear resistance, predominantly used in pipework systems. However, it suffers from low thermal conductivity, which limits its application in geothermal heating/cooling systems. In this work, crosslinked high‐density polyethylene (PEX) composites with spherical graphite (SG) as a reinforcing filler are examined in terms of their thermal and mechanical properties. Thermal conductivity measurements showed a significant improvement of the thermal conductivity of PEX with increasing filler content (40.6% augmentation for 5 wt% SG content), while the experimental data are in good agreement with the Chauhan theoretical model for spherical particles. Tensile tests revealed that the elastic modulus of PEX/SG composites presented a considerable improvement (23.6% augmentation for 5 wt% SG content). Various micromechanical models for the prediction of the composites' elastic behavior were applied to the experimental data, which present a satisfactory agreement with the Takayanagi I two‐phase model for low concentrations of SG, and the Takayanagi II two‐phase model for higher filler content. Abstract : PEX pipes used for domestic heating/cooling systems. The addition of graphite fillers in the PEX matrix provides improved thermal conductivity and enhanced mechanical properties, optimizing the pipes' utilization.